Revitalizing the Arboretum Tourist Park: Transformative skills education for sustainable community development in Bumi Harapan - Nurlaela Nurlaela; Danti Yuliarsi Saadjad; Dian Puspapratiwi (University of Merdeka Malang, 2024)
Bumi Harapan village is located in West Toili District, Banggai Regency, Central Sulawesi Province possessing strategic nature potential. Responding to the potential, the Village Government has built an education-based tourist destination along the riverside called the Arboretum Tourist Park. Yet, this project met significant obstacles so it has not optimally developed as the Village Government planned before. To solve the problems, the community service team through the Community Partnership Empowerment program revitalized the Arboretum Tourist Park by integrating transformational skills education to develop a more sustainable community in Bumi Harapan village. In this community service project, the team implemented an Asset-Based Community Development (ABCD) approach. It focuses on community empowerment in managing existing assets, which is the Arboretum Tourist Park. The results of the project indicated an enhancement in the quality of the Arboretum Tourist Park which attracted more visits of local tourists. Besides, educating the Village-Owned Enterprises, the Wana Sari team with transformative skills has provided them with essential knowledge and skills to realize more effective management of the Arboretum Tourist Park. This community service program has contributed not only to the quality enhancement of the Arboretum Tourist Park but also to a progressive strengthening of community participation in managing sustainable tourism.